2017
DOI: 10.15829/1560-4071-2017-10-85-92
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the Angiotensin Gene Polymorphism (Agt, Rs699) With Systemic Hypertension and Its Risk Factors in Gornaya Shoria Inhabitants

Abstract: Цель. Изучить распространенность полиморфизма гена aGt и его ассоциа-ции с риском развития артериальной гипертензии в этнических группах насе-ления Горной Шории. Материал и методы. Проведено клинико-эпидемиологическое исследова-ние компактно проживающего населения в труднодоступных районах Горной Шории (п. Ортон, п. усть-Кабырза) и поселке городского типа (п. Шерегеш). На основании поименных списков обследовано 1178 жителей указанных поселков. у 398 человек сплошным методом забрана кровь из кубитальной вены ут… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Their association has been established among the Dagestan population (Saidov et al, 2017). Mulerova et al (2017) found out the differences in associative relationship of the genotypes of AGT gene with the risk factors of arterial hypertension depending on ethnicity in the inhabitants of Gornaya Shoria.…”
Section: Introductionmentioning
confidence: 99%
“…Their association has been established among the Dagestan population (Saidov et al, 2017). Mulerova et al (2017) found out the differences in associative relationship of the genotypes of AGT gene with the risk factors of arterial hypertension depending on ethnicity in the inhabitants of Gornaya Shoria.…”
Section: Introductionmentioning
confidence: 99%